The Influence of Independent Commissioners, Audit Committees, and Audit Quality on the Integrity of Financial Reports - Suharmadi Suhrmadi; Yudhi Herliansyah; Wahyudi Widodo (PT Keberlanjutan Strategis Indonesia, 2026)
This research aims to analyze and obtain empirical evidence regarding the influence of independent commissioners, audit committees, and audit quality on the integrity of financial reports. The independent variables used in this research are independent commissioners, audit committees, and audit quality. The dependent variable used in this research is the integrity of financial reports. The data used in this research is secondary data obtained from the official website of the Indonesia Stock Exchange and the official websites of each company. The population in this study consists of 78 food and beverage companies listed on the Indonesia Stock Exchange in 2019-2024. By using a purposive sampling technique, a sample of 13 food and beverage companies listed on the Indonesian Stock Exchange was obtained. The data analysis method in this research uses descriptive statistical analysis.